La Constitución europea : manual de instrucciones / Carlos Carnero González, Maria José Martínez Iglesias y Ramón Suárez Vázquez - Martínez Iglesias, María JoséSuárez Suárez, Andrés Santiago; Carnero González, Carlos
En la cubierta: "Presentado por Josep Borrell"